2016
DOI: 10.1111/1758-2229.12362
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic fronts: transition zones for bacterioplankton community composition

Abstract: Oceanic fronts are widespread mesoscale features that exist in the boundary between different water masses. Despite the recognized importance of bacterioplankton (including bacteria and archaea) on the marine biogeochemical cycles and the ubiquitousness of fronts, the effect of frontal zones on the distribution of bacterioplankton community remains unknown. Using 16S rRNA gene sequencing coupled with a high spatial resolution analysis of the physical properties of the water masses, we demonstrate strong shifts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 43 publications
9
67
0
Order By: Relevance
“…Moreover, abrupt transitions in community structure were also detected, like one LG community in the Costa Rica dome (Figure ), an upwelling zone caused by a persistent cyclonic eddy (Fiedler, ), or that in front of Rio de Janeiro (Brazil), which coincided with a change in water masses due to salt finger intrusions (Fernández‐Castro et al, ). This agrees with previous smaller‐scale studies showing that oceanic fronts and mesoscale features delimit the distribution of bacterioplankton in the ocean (Baltar, Arístegui, Gasol, Lekunberri, & Herndl, ; Baltar et al, ; Flaviani et al, ). Our results further suggest that the surface tropical and subtropical global ocean represents a relatively homogeneous habitat that results in similar SpAD‐based community structures featuring small pools of dominant taxa with cosmopolitan distributions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, abrupt transitions in community structure were also detected, like one LG community in the Costa Rica dome (Figure ), an upwelling zone caused by a persistent cyclonic eddy (Fiedler, ), or that in front of Rio de Janeiro (Brazil), which coincided with a change in water masses due to salt finger intrusions (Fernández‐Castro et al, ). This agrees with previous smaller‐scale studies showing that oceanic fronts and mesoscale features delimit the distribution of bacterioplankton in the ocean (Baltar, Arístegui, Gasol, Lekunberri, & Herndl, ; Baltar et al, ; Flaviani et al, ). Our results further suggest that the surface tropical and subtropical global ocean represents a relatively homogeneous habitat that results in similar SpAD‐based community structures featuring small pools of dominant taxa with cosmopolitan distributions.…”
Section: Discussionsupporting
confidence: 92%
“…We thus hypothesize that bacterial communities are composed of taxa displaying a continuum of spatial distribution patterns, ranging from highly ubiquitous to rare and endemic, and that variations in their contribution to communities will reflect shifts in fundamental structuring processes linked to habitat transitions or dispersal barriers in the ocean (e.g., Baltar, Currie, Stuck, Roosa, & Morales, ). To test this hypothesis, we characterized the SpAD‐based structure of the prokaryotic communities across the global subtropical and tropical surface ocean.…”
Section: Introductionmentioning
confidence: 99%
“…2A, B). The boundary positions between the different water masses determined in this study are consistent with previous oceanographic surveys (Baltar et al, 2016;Baltar et al, 2015;Currie et al, 2011;Jones et al, 2013;Van Hale and Frew, 2010). The location of the front is known to oscillate seasonally, being furthest inshore in the summer (ranging from 28-40 km offshore) and farthest offshore in the winter, ranging from 35 to 50 km (Jillett, 1969;Jones et al, 2013).…”
Section: Resultssupporting
confidence: 89%
“…This site has been continuously sampled for physicochemical parameters for almost two decades (Currie and Hunter, 1999;Currie et al, 2011). Samples for this study were collected in two single-day cruises, on the 10th of March and the 21st of April of 2015, on board the RV Polaris II, and targeted 8 stations matching with previous research (Baltar et al, 2016;Baltar et al, 2015;Currie et al, 2011;Gault-Ringold et al, 2012;Jones et al, 2013). Continuous surface temperature and salinity measurements were collected along the transect using a Sea Bird SBE45 thermosalinograph and associated SBE38 remote temperature sensor, with position information appended from the vessel GPS system.…”
Section: Study Site and Samplingmentioning
confidence: 99%
“…Recent studies have endeavored to define oceanic biomes based on microbial data (e.g., Zwirglmaier et al, 2008;Zinger et al, 2011;Gibbons et al, 2013), while other studies have shown that fronts can enhance microbial activity (e.g., Arístegui and Harrison, 2002) or delimit the distribution of the bacterioplankton community composition in surface waters (Baltar et al, 2016). However, there is almost no information on how surface frontal systems influence the distribution of microbial community composition and activity in the dark water column, which contains around 75% of the prokaryotic biomass and 50% of the prokaryotic production of the global ocean ).…”
Section: Introductionmentioning
confidence: 99%